The Soy Isoflavones for Reducing Bone Loss (SIRBL) Study: Three year effects on pQCT bone mineral density and strength measures in postmenopausal women - SHEDD-WISE, KRISTINE M. (2011)
Soy isoflavones exert inconsistent bone density-preserving effects, but the bone strength-preserving effects in humans are unknown. Our double-blind randomized controlled trial examined two soy isoflavone doses (80 or 120 mg/d) vs placebo tablets on volumetric bone mineral density (vBMD) and strength (via peripheral quantitative computed tomography) in healthy postmenopausal women (46–63 y). We measured 3 y change in cortical (Ct) BMD, cortical thickness (CtThk), periosteal circumference (PC), endosteal circumference (EC), and strength-strain index (SSI) at 1/3 midshaft femur (N=171) and trabecular (Tb) BMD, PC, and SSI at 4% distal tibia (N=162). We found no treatment effect on femur CtThk, PC, or EC, or tibia TbBMD or PC. Strongest predictors (negative) of tibia TbBMD and SSI and femur CtBMD were timepoint and bone resorption; whole body fat mass was protective of SSI. As time since last menstrual period (TLMP) increased (p=0.012), 120 mg/d was protective of CtBMD. Strongest predictors of femur SSI were timepoint, bone resorption, and TLMP (protective). Isoflavone tablets were negative predictors of SSI, but 80 mg/d became protective as bone turnover increased (p=0.011). Soy isoflavone treatment for 3 y was modestly beneficial for midshaft femur vBMD as TLMP increased, and for midshaft femur SSI as bone turnover increased.